2021
DOI: 10.1111/joim.13287
|View full text |Cite
|
Sign up to set email alerts
|

Founder effects facilitate the use of a genotyping‐based approach to molecular diagnosis in Swedish patients with familial hypercholesterolaemia

Abstract: Aim To investigate whether genotyping could be used as a cost‐effective screening step, preceding next‐generation sequencing (NGS), in molecular diagnosis of familial hypercholesterolaemia (FH) in Swedish patients. Methods and results Three hundred patients of Swedish origin with clinical suspicion of heterozygous FH were analysed using a specific array genotyping panel embedding 112 FH‐causing mutations in the LDLR, APOB and PCSK9 genes. The mutations had been selected from previous reports on FH patients in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…APOB has been identified as a causative gene of familial hypercholesterolemia (FH) ( 23 , 24 ). The investigation from Benedek et al ( 25 ) showed that APOB c.10580G>A is the most common mutation in Swedish patients with FH. The agnostic genetic investigation by Zuber et al ( 26 ) prioritized APOB as a key lipid risk factor for coronary artery diseases.…”
Section: Discussionmentioning
confidence: 99%
“…APOB has been identified as a causative gene of familial hypercholesterolemia (FH) ( 23 , 24 ). The investigation from Benedek et al ( 25 ) showed that APOB c.10580G>A is the most common mutation in Swedish patients with FH. The agnostic genetic investigation by Zuber et al ( 26 ) prioritized APOB as a key lipid risk factor for coronary artery diseases.…”
Section: Discussionmentioning
confidence: 99%